The Odd Couple Revisited: A Quantitative Analysis of Perceived CFO – CEO Relationships in SDA North American Division Conferences - Brown Sr., Theodore; Lai Hing, Jean E. (Archives of Business Research, 2017)
Historically, CFOs and CEOs functioned in their own office silos, however, changes in how CFOs and CEOs relate to and work together in their organizations occurred due to the impact of Sarbanes-Oxley Act. The purpose of this paper is to examine CFO-CEO relationship data collected from SDA Conferences in North America utilizing Descriptive Statistics, ANOVAs and Chi-Square Analysis.